2014
DOI: 10.1097/aap.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Midazolam-Induced Peripheral Nerve Block and Neurotoxicity

Abstract: Our results indicate that processes underlying midazolam-induced nerve block and neurotoxicity are separable, and suggest that selective activation of TSPO may facilitate modality-selective nerve block while minimizing the potential for neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Preservatives added to steroids such as benzyl alcohol and propylene glycol have known neurolytic effects, so it is important to avoid steroid adjuvants with any preservatives (preservative-free dexamethasone sodium phosphate is recommended by the authors). Midazolam, acting primarily as a GABA-A agonist, was previously thought to attenuate nerve blockade by acting at peripheral GABA-A receptors 19 , although this more recently has been attributed to TSPO activation 7 .…”
Section: Clonidine-buprenorphine-dexamethasonementioning
confidence: 99%
See 1 more Smart Citation
“…Preservatives added to steroids such as benzyl alcohol and propylene glycol have known neurolytic effects, so it is important to avoid steroid adjuvants with any preservatives (preservative-free dexamethasone sodium phosphate is recommended by the authors). Midazolam, acting primarily as a GABA-A agonist, was previously thought to attenuate nerve blockade by acting at peripheral GABA-A receptors 19 , although this more recently has been attributed to TSPO activation 7 .…”
Section: Clonidine-buprenorphine-dexamethasonementioning
confidence: 99%
“…Steroids, such as dexamethasone, have systemic anti-nausea and anti-nociceptive effects, with possible decreased C-fiber transmission with perineural administration 6 . Midazolam, primarily known as a GABA-A agonist, may have similar pain modulation effects by acting as an agonist in the periphery via the 18 kilodalton translocator protein (TSPO) 7 , formerly known as the “peripheral benzodiazepine receptor.”…”
Section: Introductionmentioning
confidence: 99%
“…It produces central nervous system depression effects through the stimulation of γ-amino butyric acid receptors (5). To date, midazolam remains the predominant intensive care unit (ICU) sedative agent (6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on sedative drugs’ effects have mainly focused on its clinical dosages and side effects, 29 , 30 and some investigations have indicated that midazolam could induce neurotoxicity. 31 A recent study showed that midazolam can induce cancer cell apoptosis. 32 In fact, our earlier studies have shown that midazolam could briefly induce MA-10 mouse Leydig tumor cell apoptosis by activating caspase and MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%